Ciência e tecnologia na periferia: uma análise sobre parques tecnológicos e incubadoras no Brasil - Albuquerque, Andreza Dantas (Universidade Federal de São Carlos, 2019)
The proposal is to discuss, from the perspective of Science, Technology and Society (STS) approaches, the characteristics and scope of the development promoted through the promotion of Technology Parks (PqTs) and incubators of companies in Brazil, based on the analysis of policies and cases of pioneering experiences in the country, the Campina Grande (PB) and São Carlos (SP) Technology Parks Foundations. Therefore, an analysis is sought with emphasis on the following questions: What relationship is established between TQT and Development? What is the conception of Science, Technology and Innovation (CT&I) expressed (or between the lines) in public policy proposals for PqT in recent years? What is the nature of the proposed policies, their scope and dialogue with the critical demands for the country's development? What are the actors involved? The analysis is guided by the theoretical assumptions of Latin American Thought in Science, Technology and Society (PLACTS). Methodologically, the work is classified as explanatory research, using the bibliographic and documentary research methods. It uses the content analysis technique for a qualitative, critical and reflexive understanding of the cases, starting from five categories for analysis: Incubator; Technologic Park; Public resources; Partners; and Relationship with the place. Public Policy analysis uses the categories of analysis (context, content and actors) proposed by Araújo and Maciel Filho (2001). Thus, the study presents a critical look at the focus on the creation of PqTs as a development strategy for emerging countries. Subsidized by the information raised, we understand the PqTs as a controversy. The State makes use of these structures as environments capable of producing wealth and metamorphosing into development, even when the objective of the Parks is nothing more than promoting the culture of innovation and competitiveness in the business segment. The recent history of the PqTs is a failure story of the linear model of innovation. This work was carried out with the support of the Higher Education Personnel Improvement Coordination - Brazil (CAPES) - Financing Code 001.
Science and technology in the periphery: an analysis on technology parks and incubators in Brazil
Keywords: Enfoque CTS; PLACTS; Políticas públicas; Desenvolvimento; Parque tecnológico; Approaches STS; PLACTS; Development; Technologic park; Public policy; CIENCIAS HUMANAS